Adult outcomes for children of teenage mothers - Marco Francesconi (Institute for the Study of Labor (IZA), 2007)
Using data from the British Household Panel Survey, this study examines the relationship between several outcomes in early adulthood (e.g., education, inactivity, earnings, and health) and being born to a teenage mother. Besides standard cross-sectional multivariate regression estimates, we also present evidence from nonparametric estimates and from estimates that account for unmeasured family background heterogeneity by comparing siblings born to the same mother who timed their births at different ages. Regardless of the econometric technique, being born to a teenage mother is usually associated with worse outcomes. An important channel of transmission of this adverse effect is childhood family structure, which plays a more powerful role than childhood family poverty. Albeit smaller, some of the detrimental effects are also found for children of mothers who gave birth in their early twenties.
urn:nbn:de:101:1-20080401528
Keywords: 330; Familiensoziologie; Generationenbeziehungen; Mütter; Altersgruppe; Großbritannien